Determinants of the Regional Innovation Index in the VUCA Era: A Robust Regression MM-Estimation Approach - Erina Herwindalita; Siskarossa Ika Oktora (Jurnal Natural, 2026)
The world is experiencing rapid changes, making it more complex and difficult to predict. This situation is called the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) Era. Therefore, the demand for rapid adaptation through innovation is greater. However, data from the World Intellectual Property Organization shows that Indonesia's innovation index in 2022 still ranked 75th of 132 countries. It indicates that Indonesia still faces challenges and weaknesses in managing the innovation cycle, particularly in government innovation. Consequently, it is crucial to conduct research on local government innovation by identifying the determinants of the regional innovation index (RII) in 2022. In this research, robust regression with MM-estimation was used to address outlier issues in the data. The result shows that the digital skills score, degree of fiscal decentralization, and innovation capability scores have a significant positive effect on the RII in 2022. Meanwhile, the high school education completion rate and the ratio of students and lecturers have a significant negative effect on the RII in 2022.